Lactation duration and development of type 2 diabetes and metabolic syndrome in postpartum women with recent gestational diabetes mellitus - Sasiwan Suthasmalee; Chadakarn Phaloprakarn (BMC, 2024)
Abstract Background The World Health Organization and United Nations Children's Fund recommend exclusive breastfeeding (EBF) for the first six months of an infant's life. Although evidence suggests that maintaining breastfeeding has positive impacts on glucose and lipid metabolism in postpartum women with a history of gestational diabetes mellitus (GDM), no study has investigated whether such effects differ between breastfeeding intensities. This study aimed to evaluate the impact of maintaining breastfeeding on prediabetes, type 2 diabetes mellitus (T2DM), and metabolic syndrome (MetS) six months postpartum in women with GDM. This study also examined the potential variations in glucometabolic outcomes between EBF at six months and partial breastfeeding at six months. Methods This prospective cohort study included 130 women with recent GDM who experienced live births between 7 September 2020 and 31 January 2023 at a university hospital in Bangkok, Thailand. All the women were free of T2DM and MetS at baseline (six weeks postpartum). We followed up these women six months postpartum to assess their breastfeeding practices (EBF at six months, partial breastfeeding at six months, or not maintaining breastfeeding) and evaluate their progression to prediabetes, T2DM, and MetS. Maintaining breastfeeding was defined as breastfeeding for six months. EBF was determined using the "recall since birth" method. Results Of the 130 participants included, the rates of prediabetes, T2DM, and MetS six months postpartum were 33% (n = 43), 2% (n = 3), and 17% (n = 22), respectively. In the unadjusted model, maintaining breastfeeding was associated with a reduction in the risks of prediabetes and MetS but not T2DM. After adjusting for potential confounders, maintaining breastfeeding was a significant protective factor only for prediabetes. The adjusted risk ratios and 95% confidence intervals were 0.54 (0.29, 0.99) for prediabetes and 0.47 (0.19, 1.06) for MetS. When EBF at six months and partial breastfeeding at six months were separately analyzed, the risks of prediabetes and MetS differed between the two groups. In the EBF at six months-to-partial breastfeeding at six months comparison, the adjusted risk ratios (95% confidence intervals) of prediabetes and MetS were 0.46 (0.22, 0.97) vs. 0.79 (0.25, 2.49) and 0.34 (0.11, 0.99) vs. 0.69 (0.22, 2.07), respectively. Conclusions Maintaining breastfeeding reduced the risk of prediabetes and MetS, but not of T2DM, six months postpartum; these effects were significant only with EBF. These findings indicate that supporting maternal efforts to practice EBF for six months may improve women's health after GDM. Trial registration Thai Clinical Trials Registry Registration No. TCTR20200902003. Date of registration: September 2, 2020. Date of initial participant enrollment: September 7, 2020.